Informe de actividades realizadas para el proyecto PNR-CIAT en el departamento del Meta, periodo junio-diciembre 1990 - Sarria, H (International Center for Tropical Agriculture, 1991)
The cassava team in the department of Meta was strengthened. An outstanding activity was the promotion of the project in different areas of the department; San Juan de Arama was found to have great potential for agroindustrial projects. Successful trials were carried out with fresh cassava conservation using polyethylene bags and Mertect. COOAGROCASIBARE produced 14 t dried cassava in the mixed drying plant (artificial/natural), with a conversion factor of 2.73. Four seed multiplication lots were harvested and the seed distributed to governmental institutions and cooperatives. (AS (extract)-CIAT)